Use of Camphor and Essential Oil Balms for Infants in Cambodia - Bazzano, Alessandra N. (J Trop Pediatr, 2017)
Balms and oils containing terpenic compounds, such as camphor, menthol and eucalyptus, are potentially toxic, and numerous reports of adverse events stemming from their use in infants and young children have been published. During qualitative research on newborn practices in rural Cambodia, these products were found to be commonly applied to the skin of newborns and infants and available in most households. Parents and caregivers of infants in Cambodia and other settings where use of camphor- and menthol-containing products are common should be educated on the risks of these to prevent child morbidity and potential mortality.